Tracking the Fossil Footprints and Letters of Science from Doctor E. F. Harding in Windsor, Nova Scotia: 1842-1855 - Fedak, Tim (Scientia Canadensis)

(untitled) (CSTHA/AHSTC, 2021)
Three hand-written letters from Dr. Ebenezer Fitch Harding to J. W. Dawson between 1845 and 1855 provide an example of the “collective” aspect of early geology. Dr. Harding was a community physician in Windsor, Nova Scotia, when he accompanied Charles Lyell during Lyell’s visit to the geology sites and mud flats of the Minas Basin, Bay of Fundy in the summer of 1842. The three letters span the period at the dawn of Nova Scotia geology and give insight into Dr. Harding’s personal interest, contributions to science, and relationship with Dawson in Pictou, Nova Scotia. Examination of the transcribed letters document this important period in Nova Scotia geology, demonstrate linkages between Nova Scotia and Edinburgh, and suggest future work to consider the development of the visual language of geology in Nova Scotia. The history and status of a fossil trackway named by Dawson as Hylopus hardingi provides further insights into the nature of collections and collaborations between Harding and Dawson.